2019
DOI: 10.1093/ajcn/nqz201
|View full text |Cite
|
Sign up to set email alerts
|

Changes in micronutrient and inflammation serum biomarker concentrations after a norovirus human challenge

Abstract: Background To accurately assess micronutrient status, it is necessary to characterize the effects of inflammation and the acute-phase response on nutrient biomarkers. Objective Within a norovirus human challenge study, we aimed to model the inflammatory response of C-reactive protein (CRP) and α-1-acid glycoprotein (AGP) by infection status, model kinetics of micronutrient biomarkers by inflammation status, and evaluate assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 54 publications
1
26
0
2
Order By: Relevance
“…Hepcidin, Hypoferremia, and Viral Infections Hepcidin-controlled iron redistribution protects against some bacterial infections and malaria in mice. 29,30 In humans, increased hepcidin and hypoferremia occur after experimental norovirus, typhoid, and malaria infections, [31][32][33] and during the initial emergence of viremia in HIV-1-infected blood donors. 34 Although inflammatory hypoferremia can be beneficial in the context of infections with single-cell organisms that must acquire iron from their host, evidence that low serum iron is protective in the context of viral infections is lacking.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…Hepcidin, Hypoferremia, and Viral Infections Hepcidin-controlled iron redistribution protects against some bacterial infections and malaria in mice. 29,30 In humans, increased hepcidin and hypoferremia occur after experimental norovirus, typhoid, and malaria infections, [31][32][33] and during the initial emergence of viremia in HIV-1-infected blood donors. 34 Although inflammatory hypoferremia can be beneficial in the context of infections with single-cell organisms that must acquire iron from their host, evidence that low serum iron is protective in the context of viral infections is lacking.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…Although we did not directly show the effect of HDIVC on cytokines, we have demonstrated the shorter duration of SIRS and less SIRS prevalence in the HDIVC compared to the control group during the first week after admission. Serum levels of CRP are usually used to track and monitor the inflammatory response caused by infection due its short half-life of 19 h (Williams et al, 2019). CRP levels were shown to be reduced rapidly by HDIVC (200 mg/kg/day) in a previous before-after study in a cohort of sepsis patients (Fowler et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from longitudinal studies support the changes we have observed in micronutrient biomarker concentrations related to the acute-phase proteins. For example, in a norovirus challenge study of healthy adults, ferritin concentrations increased, and retinol and RBP concentrations decreased, in response to temporary elevations in AGP and CRP ( 25 ). No changes in micronutrient biomarkers were observed among uninflamed individuals over time, which further suggests that iron and vitamin A biomarker concentration changes in the inflamed group were temporal and not reflective of underlying nutritional status ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a norovirus challenge study of healthy adults, ferritin concentrations increased, and retinol and RBP concentrations decreased, in response to temporary elevations in AGP and CRP ( 25 ). No changes in micronutrient biomarkers were observed among uninflamed individuals over time, which further suggests that iron and vitamin A biomarker concentration changes in the inflamed group were temporal and not reflective of underlying nutritional status ( 25 ). A study among asymptomatic children in Burkina Faso found that short-term, within-individual changes in ferritin and RBP in relation to AGP and CRP were similar to between-individual cross-sectional differences, supporting the validity of inflammation adjustment approaches in cross-sectional surveys ( 26 ).…”
Section: Discussionmentioning
confidence: 99%